Hindered cytoplasmic diffusion of inositol trisphosphate restricts its cellular range of action - Dickinson, George D. (2016)
The range of action of intracellular messengers is determined by their rates of diffusion and degradation. Previous measurements in oocyte cytoplasmic extracts indicated that the Ca2+-liberating secondmessenger inositol trisphosphate (IP3) diffuses with a coefficient (∼280 mm2 s-1) similar to that in water, corresponding to a range of action of ∼25 mm. Consequently, IP3 is generally considered a "global" cellular messenger. We reexamined this issue by measuring local IP3-evoked Ca2+ puffs to monitor IP3 diffusing from spot photorelease in neuroblastoma cells. Fitting these data by numerical simulations yielded a diffusion coefficient (≤10 mm2 s-1) about 30-fold slower than that previously reported. We propose that diffusion of IP3 in mammalian cells is hindered by binding to immobile, functionally inactive receptors that were diluted in oocyte extracts. The predicted range of action of IP3 (<5 mm) is thus smaller than the size of typical mammalian cells, indicating that IP3 should better be considered as a local rather than a global cellular messenger. 2016